Assessment of Animal Sensitivity to Particularly Dangerous Orthopoxviruses, Using Primary Cultures of Lung Cells - A. S. Zamedyanskaya; Al. A. Sergeev; K. A. Titova; A. S. Kabanov; L. E. Bulychev; Ar. A. Sergeev; A. E. Nesterov; O. V. Nosareva; D. O. Galakhova; L. N. Shishkina; A. P. Agafonov; A. N. Sergeev (Проблемы особо опасных инфекций, 2016)
Objective of the study is to investigate the sensitivity of different animals to highly pathogenic Orthopoxviruses applying techniques, based on utilization of primary cultures of lung cells, and to assess the possibility of further deployment of this approach. Materials and methods. Cultural and virological research methods are used. Results and conclusions. Performed is the assessment of sensitivity of outbred mice, marmots and chickens to variola virus (VV) and monkeypox virus (MPV), using suspended primary cultures of lung cells (SPCLC) of these animals. Through inoculation of the mentioned above cell cultures with VV and MPV in a dose of 0.00001 PFU per a cell (plaque forming unit /cell) demonstrated has been virus replication with maximum concentration values in all cases (1,4 - 2,0 lg PFU/ml), mainly 3 days after infection. According to the data on SPCLC, sensitivity to VV in mice, marmots and chickens (ID50 - 50 % infective dose) amounts to (1,3 ± 0,5) lg PFU; (2,3 ± 0,5) lg PFU; and (0,0 ± 0,4) lg PFU respectively, taking into account unhindered interaction of the virus with permissive lung cells in the organism of the animals. As for MPV values for this indicator, they are: (1,7 ± 0,3) lg PFU for mice, and (0,5 ± 0,3) lg PFU - for marmots. Obtained ID50 values for VV using mice SPCLC and for MPV using mice and marmots SPCLC coincide with the ones, studied in direct experiments on intranasal infection with the viruses, with regard to 10 % of the viral application in lungs when deploying the latter method of infection. The fact testifies to the possibility of further deployment of this method for the assessment of animal sensitivity to highly pathogenic Orthopoxviruses based on the results of in vitro experiments.